2022
DOI: 10.22541/au.166069342.27133443/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SARS-CoV-2 Spike Protein in the Pathogenesis of Prion-like Diseases

Abstract: Human prion protein and prion-like protein misfolding are widely recognized as playing a causal role in a large and growing number of neurodegenerative diseases. Here we summarize the compelling evidence that the spike protein of SARS-CoV-2 contains extended amino acid sequences previously established as characteristic of a prion-like protein. This suggests that vaccine-induced spike protein production is synonymous with production of a prion-like protein, and we trace some of the various pathways through whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 90 publications
1
2
0
Order By: Relevance
“…The same prion domain is present in the SARS-CoV-2 mRNA vaccine and has been implicated in the genesis of recently reported cases of SARS -CoV-2 vaccine -induced new form of a rapidly progressive Creutzfeldt-−Jakob disease phenotype. This further augments the notion of SARS – CoVSARS-CoV potential for inducing protein misfolding and fibrillogenesis in some vulnerable subjects [ 24 , 25 ].…”
Section: Discussionsupporting
confidence: 58%
“…The same prion domain is present in the SARS-CoV-2 mRNA vaccine and has been implicated in the genesis of recently reported cases of SARS -CoV-2 vaccine -induced new form of a rapidly progressive Creutzfeldt-−Jakob disease phenotype. This further augments the notion of SARS – CoVSARS-CoV potential for inducing protein misfolding and fibrillogenesis in some vulnerable subjects [ 24 , 25 ].…”
Section: Discussionsupporting
confidence: 58%
“…The Author further found that at least one COVID-19 vaccine was associated with an increased risk of Parkinson's disease [60], a prion related disease. Additional authors have confirmed that the spike protein, the active ingredient in COVID-19 vaccines, also contains amino acid sequences capable of inducing prion disease and have reported patients developing prion disease after receiving a COVID vaccine [61][62][63].…”
Section: The Death Of Suzanne Eaton [45] In July Of 2019 First Led Thementioning
confidence: 99%
“…There is little doubt that the COVID "vaccines" cause prion disease. Both the "vaccine" mRNA sequence [1] and the "vaccine" induced spike protein [2,4,5] have the ability to induce prion disease. A number of groups have reported prion disease in patients after receiving the COVID "vaccine".…”
Section: Introductionmentioning
confidence: 99%